LINEAMENT EXTRACTION AND THE CORRELATION TO VEGETATION AND MOISTURE INDICES FOR GROUNDWATER PREDICTION IN BENGKULU SELATAN REGENCY, INDONESIA - Setiawan, Budhi; KAMIL, FADHELLATUL (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2022)
Lineament representsthe geological features in response to a weak zone that might manifestgroundwater potential. The researchaims to determine the relationship between the lineament extraction andvegetation and surface moisture indices. The study was conducted in South Bengkulu, Bengkulu, based on Shaded Relief images at azimuth 0o, 45o, 90o, and 135ofrom Digital Elevation Model (DEM) image processing through DEMNAS (8 meters). Then, analysis of vegetation and moisture indices using Normalized Difference Vegetation Index (NDVI), Normalized Difference Moisture Index (NDMI), and Moisture Stress Index (MSI) from Landsat 8 OLI/TIRS extraction image. The Pearson Linear correlation method is used forcorrelation analysis. Based on the analysis of the lineament data, there are 12,206 lineament patterns, dominantly trending in NW-SE, N-S, and NE-SW. The lineament density parameters showthe density level 0 km/km2-10.44 km/km2. The results of the correlation of data on lineament density to the image index have positive and negative trend values, namely: NDVI (0.16), NDMI (0.37), and MSI (-0.43). From the results,the highest density is straight to the vegetation and high surface moisture. Therefore, the analysis isusefulas an initial indicator of the potential presence of groundwater. Keywords: Groundwater, lineamentremote sensing, DEM, Landsat 8